A MSFEM to simulate the eddy current problem in laminated iron cores in 3D. Issue 5 (8th August 2019) - Hollaus, Karl
Abstract : Purpose: The simulation of eddy currents in laminated iron cores by the finite element method (FEM) is of great interest in the design of electrical devices. Modeling each laminate by finite elements leads to extremely large nonlinear systems of equations impossible to solve with present computer resources reasonably. The purpose of this study is to show that the multiscale finite element method (MSFEM) overcomes this difficulty. Design/methodology/approach: A new MSFEM approach for eddy currents of laminated nonlinear iron cores in three dimensions based on the magnetic vector potential is presented. How to construct the MSFEM approach in principal is shown. The MSFEM with the Biot–Savart field in the frequency domain, a higher-order approach, the time stepping method and with the harmonic balance method are introduced and studied. Findings: Various simulations demonstrate the feasibility, efficiency and versatility of the new MSFEM. Originality/value: The novel MSFEM solves true three-dimensional eddy current problems in laminated iron cores taking into account of the edge effect.